The teacher’s opinion about professional development in the teaching of the subject musical culture - Ivković, Kristina (Norma, 2022)
The question of a permanent, lifetime worth of studying and improvement through formal, nonformal, and informal education has, in the last couple of years, become a more popular topic in various areas, including the area of education and teachers’ and professors’ professional development. In modern societies, the professional development of teachers and professors is seen as one of the key segments of contemporary education development and the development of the entire society which lies on the basis of the educational system. Individual and group professional development of teachers is a dominant form of permanent education and professional development of teachers in our country. Considering the countless potentials of Music culture instruction, and its opportunity to influence different elements of young school-age children’s development, this paper focused on examining the opinions and practical steps of teachers related to the individual and professional development in the area of Music culture. The key results of this research indicate that the participans have a mostly positive opinion towards both individual and group professional development in the field of teaching the subject Music culture. Their specific activities in the context of individual and group professional development indicate the difference between the opinions and behavior of the participants. Namely, despite the positive opinion towards individual and professional training in the field of teaching the subject Music culture, the respondents included in this research take part relatively rarely.
Keywords: permanent education; modern school; lifelong learning; primary school teachers; music